Populists, plungers, and progressives : a social history of stock and commodity speculation, 1890-1936 - Cowing, Cedric B. (Princeton legacy library., 1965)
From market memoirs, newspapers, financial journals, and Congressional records, the author has woven a narrative describing the political, social, and economic adjustment of the American people to the speculative machinery that developed between 1868 and the New Deal. The book begins with the struggle of Populist legislators, representing stable farmers, to win a Congressional ban of future commodity trading. Congress failed to act, but anti-speculation, a characteristic of Populism, remained important. In the Progressive era, the stock market rivaled the commodity exchanges for attention. Criticism of market practices was rampant as stories of Plungers spread, but no halt came until the crash. Then New Deal philosophy favored the Progressive faction of the anti-speculators. Originally published in 1965. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.